Inquiry Learning Model to Improve Student Cognitive Learning Outcomes in Temperature and Heat - Hikmawati Hikmawati; Kusmiyati Kusmiyati; Sutrio Sutrio (Jurnal Penelitian Pendidikan IPA, 2020)
This study aims to describe the effectiveness of the inquiry learning model to improve students' cognitive learning outcomes at the temperature and heat of class XI from one public school (SMAN 1 Gerung). This type of research is a quasi experiment with the basic pattern "The One Group Pretest-Posttest Design" and descriptive method. The research instrument used was the observation sheet applying the learning model and test the learning outcomes in the cognitive domain (C1 to C6). Assessment of learning implementation using a scale of 1 to 4. Student learning outcomes are said to be complete if 80% of students obtain a minimum value of 75. The results of this study indicate that: the implementation of learning increased from the criteria both in the first meeting to rise to be very good criteria at the fourth meeting. Student cognitive learning outcomes increased from 43 in the pre-test to 78 in the post-test, with classical completeness of 84%. The conclusion of this study is inquiry learning effectively improves students' cognitive learning outcomes in temperature and heat.